Mechanical abnormalities associated with first- and second-generation drug-eluting stent thrombosis analyzed by optical coherence tomography in the national PESTO French registry. (15th January 2017) - Amabile, Nicolas; Trouillet, Charlotte; Meneveau, Nicolas; Tissot, Claire Marie; Belle, Loic; Combaret, Nicolas; Range, Grégoire; Pansieri, Michel; Delaunay, Regis; Levesque, Sébastien; Lhermusier, Thibault; Derimay, François; et al.
Abstract: Background and objectives: DES thrombosis may be triggered by different mechanisms that are difficult to identify by angiography alone. This work aimed to investigate and compare the characteristics of stent thrombosis (ST) between 1st- and 2nd-generation drug-eluting stents (DES) among a large cohort of patients explored by optical coherence tomography (OCT). Methods and results: The PESTO study was a prospective national registry involving 29 French catheterization facilities. Patients with acute coronary syndromes were prospectively screened for presence of definite ST and analyzed by OCT after culprit lesion deocclusion. The analysis involved 71 subjects including 34 patients with 1st-generation DES (DES1G) and 35 patients with 2nd-generation DES (DES2G). Most patients (80%) presented with very late stent thrombosis. The median time between initial PCI and ST was longer in DES1G than DES2G patients (3.8 [2.6–6.5] years vs. 1.1 [0.04–2.3] years, p  < 0.0001). OCT identified an underlying morphological abnormality in 96% of the cases. Significant malapposition was the main abnormality observed either in DES1G (26%) or DES2G patients (35%). Ruptured neoatherosclerotic lesions were more frequently observed with DES1G than with DES2G (26% vs. 3%, p  = 0.008). There was no significant difference in percentage of malapposed struts and uncovered struts between groups. Conclusions: In this registry, DES thrombosis mainly occurred ≥ 1 year after initial PCI. OCT identified a mechanical abnormality in the vast majority of the cases. Similar causes were observed between DES1G and DES2G, but neoatherosclerotic lesions were more common in DES1G.